Impelementasi Metode Role Playing dalam Kemampuan Kreatif Siswa di Kelas IV SDN 056592 Perkebunan Bekiun - Fitri Ayu Ningsih (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Elementary education plays a crucial role in the development of students' creativity; however, conventional teaching methods often fail to optimally engage students. This research aims to examine the implementation of the role playing method in enhancing the creative abilities of fourth-grade students at SDN 056592 Perkebunan Bekiun. The study employs a classroom action research design with a qualitative approach, conducted over two cycles. Data were collected through observations, interviews, and analysis of students' work documentation. The findings indicate that the application of the role playing method significantly improved students' creative abilities, with approximately 85% of students demonstrating increased participation and confidence in expressing their ideas. Additionally, students also showed enhanced social skills, such as collaboration and communication. These results suggest that the role playing method is effective in creating a fun and engaging learning environment and can serve as an alternative approach in elementary school education.